2019
DOI: 10.1111/aas.13431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil on pleural and peritoneal effusions after the TCPC operation

Abstract: The total cavopulmonary connection (TCPC) operation is the last stage in the palliative treatment of patients with a univentricular heart malformation. Prolonged pleural and peritoneal effusions, however, remain as a significant source of morbidity after the TCPC operation. 1,2 The high pre-operative pulmonary artery pressure is a risk factor for prolonged pleural effusion. 3 Sildenafil has been used in the treatment of pulmonary hypertension. Sildenafil reduces pulmonary vascular resistance and the transpulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Some prior studies, 6 14 15 16 with the routine administration of pharmacological pulmonary vasodilator (sildenafil, iNO or milrinone) in postoperative Fontan management showed improvement in hemodynamics values in patients with elevated central venous pressure and transpulmonary pressure gradient. Our findings are in agreement with previous studies Mendoza, Koski, Collins et al 17 18 19 that reported postoperative administration of sildenafil and iNO had no influence on early postoperative clinical outcome after the modified Fontan operation.…”
Section: Discussionsupporting
confidence: 94%
“…Some prior studies, 6 14 15 16 with the routine administration of pharmacological pulmonary vasodilator (sildenafil, iNO or milrinone) in postoperative Fontan management showed improvement in hemodynamics values in patients with elevated central venous pressure and transpulmonary pressure gradient. Our findings are in agreement with previous studies Mendoza, Koski, Collins et al 17 18 19 that reported postoperative administration of sildenafil and iNO had no influence on early postoperative clinical outcome after the modified Fontan operation.…”
Section: Discussionsupporting
confidence: 94%
“…[21][22][23][31][32][33][34][36][37][38]41,43,44,46 In terms of primary outcomes, 14 studies assessed change in pulmonary pressures 21,23,[28][29][30][31][32][34][35][36]38,40,42,44 ; four assessed the incidence of pulmonary hypertensive crises, although definitions varied 22,33,37,40 ; three evaluated the requirement for additional therapy for pulmonary hypertension 26,39,41 ; and five used clinical endpoints including duration of pleural drainage (n = 3) or mechanical ventilation (n = 2), and mortality (n = 2). 24,25,27,43,45 One included study evaluated the pharmacokinetics of the investigated drug, and three evaluated a doseresponse curve. 21,23,36,46 Haemodynamic data included pulmonary arterial pressures as measured by direct pulmonary artery catheter in 13 studies, central venous pressures as measured by direct central venous catheter in six studies, atrial pressures as measured by direct atrial catheter in five studi...…”
Section: Resultsmentioning
confidence: 99%
“…31,39 However, three separate single-centre retrospective studies of 186 total children compared the effect of standardising treatment with sildenafil (starting doses range 2.1-4.6 mg/kg/day) for all children following Fontan operation with diverging results. 42,43,45 One study found sildenafil treatment to be associated with shorter duration of intubation, chest tube drainage, and ICU length of stay, but no difference in outcomes was seen in the other two studies and one suggested a more positive fluid balance on post-operative day one in children receiving sildenafil.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%
“…The first by the anesthesia group at Children's Hospital in Helsinki examined the use of sildenafil administered preoperatively the morning of surgery or within the first 24 hours after surgery on pleural and peritoneal effusions. 45 From their review, 48 patients received sildenafil and 60 were in the control group. The primary outcome measure for the study was time from the operation to the removal of drains.…”
Section: Fontan Surgery and Physiologymentioning
confidence: 99%
“…The only factor difference between the treatment and control groups to stand up to multiple regression analysis was a larger 24-hour fluid balance in the sildenafil group. 45 At our institution, many single ventricle patients are maintained on sildenafil at various stages of repair, including pre-and post-Fontan. The rationale is to lower pulmonary vascular resistance, maintain appropriate transpulmonary gradient, and thereby improve cavopulmonary blood flow and cardiac output.…”
Section: Fontan Surgery and Physiologymentioning
confidence: 99%